STEM-EDP Research Trends in Science Education: A Systematic Review from 2016 - 2025 - Syamsudin, Frendi Ihwan; Wiyono, Ketang; Patriot, Evelina Astra; Ismet, Ismet; Kamari, Azlan (JPPS (Jurnal Penelitian Pendidikan Sains), 2025)
Objective:  This study aims to analyze the research trends, characteristics, and development patterns of Science, Technology, Engineering, and Mathematics integrated with the Engineering Design Process (STEM-EDP) in Science Education from 2016 to 2025. Method: A Systematic Literature Review (SLR) combined with bibliometric analysis was conducted using VOSviewer. A total of 101 articles indexed in the Springer database were selected based on predefined inclusion and exclusion criteria. The analysis focused on annual publication trends, keyword frequency, research methods, authorship patterns, geographical distribution, citation rankings, and journal productivity. Results: The findings indicate a consistent upward trend in STEM-EDP publications, with a projected peak in 2025. Qualitative research methods dominate the field (80.19%), reflecting the exploratory nature of STEM-EDP studies. Single-authored publications are most common, while the Americas—particularly the United States—contribute the highest number of publications. The most cited authors are Kelly C. Margot and Todd Kettler (179 citations). The International Journal of Technology and Design Education is identified as the most productive journal. Keyword mapping reveals that STEM-EDP remains in an emerging research cluster, frequently associated with project-based learning and creative thinking. Novelty: This study provides a comprehensive bibliometric mapping specifically focused on STEM-EDP within Science Education using the Springer database for the 2016–2025 period. Unlike previous reviews that examined general STEM research, this study highlights the distinct integration of the Engineering Design Process and identifies emerging thematic directions and methodological gaps for future research.